Mathematical simulations and Verhulst modeling of compositional changes in DNA sequences of acquired genomic islands due to bacterial genome amelioration - Reva, Oleg N. (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.